An anaesthesiologist's encounter with purple glove syndrome - Uma, B (Indian J Anaesth, 2016)
Purple glove syndrome (PGS) is a devastating complication of intravenous (IV) phenytoin administration. Anaesthetic management during the amputation of the limb for such patients is very challenging due to limited clinical experience. A 65-year-old woman developed PGS of left upper extremity after IV administration of phenytoin following generalised tonic-clonic seizures. The condition progressed rapidly leading to gangrene of left hand extending to the mid arm. Amputation was carried out under general anaesthesia with a supraglottic airway device. We discuss the prevention and alternate managements in PGS, which is a rare clinical entity with limited data in the literature.